An MRI study of the meniscofemoral and transverse ligaments of the knee - Erbagci, H; Yildirim, H; Kizilkan, N; Gümüsburun, E (Springer-Verlag, 2002)
Our aim was to assess the anatomic localization, dimensions and incidence of the transverse and meniscofemoral ligaments, which can show anatomic variations or be mistaken for some pathologic conditions. In 100 healthy subjects (52 female, 48 male) whose ages ranged from 12 to 84 years, sagittal and coronal magnetic resonance images of the knee were obtained. There was at least one anterior or posterior meniscofemoral ligament in 82 cases. The anterior meniscofemoral ligament was present in 8 of the female and 4 of the male subjects. The posterior meniscofemoral ligament was found in 20 female and 22 male subjects. Both the anterior and posterior meniscofemoral ligaments were present in 15 female and 13 male subjects. The transverse ligament of knee was encountered in 19 female and 12 male subjects. In the females, average lengths of the anterior and posterior meniscofemoral ligaments were 9.87 +/- 4.79 mm and 25.60 +/- 5.50 mm, respectively. The corresponding values in the males were 11.11 +/- 2.57 mm and 28.80 +/- 5.49 mm, respectively. In the females, average width of the anterior and posterior meniscofemoral ligaments were 2.45 +/- 1.02 mm and 2.30 +/- 1.15 mm, respectively. The corresponding values in the males were 2.52 +/- 0.87 mm and 2.30 +/- 1.15 mm, respectively. On MRI assessment, in order to differentiate intra-articular lesions such as osteochondral and meniscal fragments or pseudotear of the lateral meniscus from the normal ligamentous anatomy of knee, the orientation and characteristic localization of the meniscofemoral ligaments should be taken into account.
Keywords: meniscofemoral ligament; transverse ligament of knee; MRI; knee